Development and verification of the commercial value added chain of content marketing response - Hirschfelder, Benedikt (School of Management Studies, 2019)
The rapid technological progress in the last 10 years and the coherent opportunities for consumers to communicate among each other almost borderless 24/7, also impacted marketing strategies. Whereas accentuation of product values and pricing are still valuable marketing strategies, consumers are due to the 24/7 access to knowledge, information and consumer feedback, desensitized when it comes to advertising. Availability of the internet across borders, all the time is the main driving factor for marketing practitioners to progressively try to build up a non-purchase pushing relationship to the consumer. With the content communicated in the foreground (informative, helpful or entertaining) and the commercial message in the background this marketing strategy is also known as Content Marketing. Whereas the use of Content Marketing in corporate world is relatively popular, academic research is relatively rare. Indeed, some research was conducted on storytelling and signature stories -a tool of Content Marketing-, however, the functionality of the generic term Content Marketing resembles rather a black box. With the aim to illuminate the understanding and functionality of Content Marketing, this study explored the coherences between content communication vehicles and content generating vehicles. In the scope of this thesis, a theoretical framework conceptualizes the commercial value added chain of Content Marketing response was developed and verified in a business to consumer scenario. This theoretical framework was substantiated with a real world application, more precisely the 'Be More human’ video campaign from the sportswear manufacturer Reebok served as a research object. A non-probability sampling frame, using convenience sampling resulted in a total sample size of 750 respondents. Since this study focused on the development and testing of a theory, partial least square - structural equitation modelling (PLS-SEM) was applied using the software package SmartPLS3. Through the development of the commercial value added chain of Content Marketing response this study exemplifies the commercial content generation process and the content value added by the consumer and thus contributes to a better understanding in academia as well as in corporate world of the complex generic term Content Marketing.